2002
DOI: 10.1177/145749690209100205
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Vascular Disease as Predictor of Outcome after Coronary Artery Bypass Grafting

Abstract: Background and Aims: Understanding and objective assessment of risks is crucial in cardiac surgery. The aim of this study was to assess the influence of peripheral vascular disease (PVD) on morbidity, mortality and outcome in coronary artery bypass grafting (CABG) patients.Material and Methods: The ankle-brachial pressure index (ABPI) was used as indicator of PVD and was measured in 178 CABG patients. Two groups were established: 1. normal ABPI (0.9-1.3) (n =136) and 2. lowered ABPI (< 0.9) (n =35). The mean f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
8
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
3
8
0
Order By: Relevance
“…22 Peripheral vascular disease has been linked with major leg wound complications, including amputation, after vein harvest. 42 Similar to previous findings, we found that PVD is not associated with short-term complications, including leg wound infection, after CABG procedures. 42 Similar to previous findings, we found that PVD is not associated with short-term complications, including leg wound infection, after CABG procedures.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…22 Peripheral vascular disease has been linked with major leg wound complications, including amputation, after vein harvest. 42 Similar to previous findings, we found that PVD is not associated with short-term complications, including leg wound infection, after CABG procedures. 42 Similar to previous findings, we found that PVD is not associated with short-term complications, including leg wound infection, after CABG procedures.…”
Section: Discussionsupporting
confidence: 92%
“…22,42 Twenty percent of our population had documented preexisting PVD, which is consistent with previous research. 42 This may relate to varying definitions of PVD and chronic renal insufficiency, and how the data on these two conditions were collected both in the literature and during our project. 42 This may relate to varying definitions of PVD and chronic renal insufficiency, and how the data on these two conditions were collected both in the literature and during our project.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the investigators did not make any distinction between clinical or subclinical PAD. For the short-term prognosis, a Finnish study (13) of 178 CABG patients presented low ABI predictive of postoperative myocardial infarction and atrial fibrillation, without any distinction according to clinical status or elevated ABI. To our knowledge, our study is the first providing evidence on the additive predictive power of ABI to the clinical presence of PAD.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that beyond clinical PAD, a larger group of people present with subclinical PAD, which is generally defined by a low ankle-brachial index (ABI). Data on the utility of ABI measurement for the risk stratification of patients undergoing CABG are scarce (12,13).…”
mentioning
confidence: 99%
“…[35] Patients with a PVD history undergoing CABG had more coexistent risk factors. [363738] The another study showed that these patients also exhibited higher rates of cardiac, systemic, and pulmonary complications. [36]…”
Section: Discussionmentioning
confidence: 99%